[Spichlerze nad Motławą] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia spichlerze na Ołowiance, widok od strony Motławy, w głębi widoczne budynki mieszkalne, ok. 1910 r.